Techniques and quality of translation of cultural terms in Indonesian folktales: Study Let’s Read platform - Indika Khoifin; Yeni Artanti (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2026)
Translating cultural terms is essential for ensuring accurate and effective cultural transfer in reading materials. This study aimed to analyze cultural terms, translation techniques, and translation quality in children’s folklore books available in the Let’s Read digital library. The study employed a mixed-methods design using a concurrent embedded approach. The sample consisted of 15 folklore books from the Let’s Read platform, along with informants including English speakers, teachers, and parents. The data comprised qualitative data namely cultural terms and translation techniques collected through content analysis sheets and interviews, as well as quantitative data on translation quality gathered through assessment sheets. Qualitative data were analyzed with content analysis and quantitative data descriptively. The results showed that the most prevalent cultural specifics found were related to material culture and social culture. On the other hand, borrowing was the most frequent translation procedure found in children’s folklore texts on Let’s Read platform. Last, the average of translated evaluation score is 2.49 which was relatively acceptable in terms of describing quality and adequacy, but there were still some aspects which could be further improved with respect to translatability and acceptability especially regarding its readability.